Capacity Building of Rural Women in Dairy Farming : An Impact Assessment - Akila N and Senthilvel K, (Indian Journal of Extension Education, 2013)
The study on adoption of dairy farming technologies by rural women in Karur district of Tamil Nadu revealed that the ruralwomen were involved in all activities to take care of the animals except decision regarding marketing milk, purchase andsale of animals. Green fodder production (24%), pregnant animal care (21%), importance of deworming (19%),maintaining dry period (9%), and clean milk production (5%) were the technologies least adopted by the respondentsbefore training. After the training, considerable improvement was seen among the trainees in adopting the technologieslike deworming (96%), artificial insemination (98%), vaccination and mineral mixture feeding (97%). Lack ofremunerative price for milk is the major constraint faced by the respondents followed by high cost of feed.